Projections : Comics and the History of Twenty-First-Century Storytelling. - Gardner, Jared (Post 45., 2012)
When Art Spiegelman's Maus won the Pulitzer Prize in 1992, it marked a new era for comics. Comics are now taken seriously by the same academic and cultural institutions that long dismissed the form. And the visibility of comics continues to increase, with alternative cartoonists now published by major presses and more comics-based films arriving on the screen each year. Projections argues that the seemingly sudden visibility of comics is no accident. Beginning with the parallel development of narrative comics at the turn of the 20th century, comics have long been a form that invites--indeed req.